Identification of PTP1B dynamics using frequency response analysis - Eren, Dilek. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
Protein tyrosine phosphatase 1B (PTP1B) plays a key role as negative regulator of insulin and leptin signaling. In human PTP1B, a significant conformation change is seen in the WPD loop from open (inactive) to closed (active) conformation, when a ligand is bound to the enzyme. The aim of this study is to see how functionally important distant portions, such as S-loop, are perturbed by disturbances in the active site, and suggest a method which could be utilized to find communication pathways between distant regions in a protein, using frequency response techniques. Therefore, five different periods of TMD simulation cycles (one closing-opening motion of WPD loop) were applied between WPD loop in open (WPDopen) and in closed (WPDclosed) conformations of PTP1B. TMD potential force is applied on the WPD loop and the R-loop Using Discrete Fourier Transform to filter out the perturbed frequency components from random fluctuations, it was observed that the effects of this continuous periodic excitation of the active site spread throughout the whole protein, manifesting itself with increase in mobility of distant regions. Increase in fluctuations are seen not only in the vicinity of WPD loop and R- loop, but also at some distant parts of PTP1B, not directly in contact with the active site or WPD loop, i.e. α1', α2', pTyr recognition loop, R-loop, L11, WPD loop, α3, P-loop, Q-loop and α6. Moreover, most of the displacements of the residues are practically in the same direction with those of the crystal structures. A surprising result is also obtained in the functionally important region, S-loop. Although there is no mobility increase in S-loop with respect to equilibrium MD simulations, opening/closing of WPD loop makes the first eigenvector of S-loop displacements at the base frequency of oscillations more aligned with that between the crystal structures. This result shows that allostericity is not always manifested as increase in residue mobility, but also in adjustment of the directionality of residue fluctuations. TMD simulations at higher frequencies of WPD loop motions show that amplitude of oscillations of many of the distant regions, and even the active site, decreases, as that would be expected from a linear system.
Keywords: Protein-tyrosine phosphatase.